Skeletal isomerization of octadecane on bifunctional ZSM-23 zeolite catalyst - Huybrechts, Ward; Vanbutsele, Gina; Houthoofd, Kristof J.; Bertinchamps, Fabrice; Laxmi Narasimhan, C. S.; Gaigneaux, Eric M.; Thybaut, Joris W.; Marin, Guy B.; Denayer, Joeri F. M.; Baron, Gino V.; Jacobs, Pierre A.; Martens, Johan A. (Catalysis letters, 2005)
Octadecane was isomerized over three different Pt/H-ZSM-23 samples. The distributions of methylheptadecane and dimethylheptadecane skeletal isomers obtained on the Pt/ZSM-23 samples were very similar. Positional isomer distributions are fingerprints of the zeolite framework structure. The independence of skeletal isomer distributions from Al-gradients and particle size constitutes a strong argument in favor of pore-mouth catalysis.